Extracellular matrix change in patients with various forms of atrial fibrillation - Goryachiy, A. V.; Gozhenko, A. I.; Levchenko, E. M.; Goriachyi, V. V.; Kuznetsova, M. A.; Arapu, M. I. (Journal of Education, Health and Sport, 2017)
Purpose: We studied the change in serum collagen markers in patients with various forms of atrial fibrillation (AF)Methods: Collagen type C-terminal propeptide (CTPK-I), C-terminal telopeptide of type I collagen (CTTK-I), matrix metalloproteinase I, and tissue inhibitors of matrix metalloproteinase I were used as markers for collagen synthesis. The study group comprised - 70 people, control - 20.Results: The level of CTCP-I and CTTP-I in patients with AF was significantly higher in comparison with the control group (91 +27 ng / ml, 67 + 11 ng / ml, p <0.001 and 0.38 + 0.20 ng / ml, 0.25 +0.08 ng / ml, p <0.001, respectively). The level of TSCP-I in patients with persistent and chronic AF was significantly higher (105 +28 ng / ml and 126 + 26 ng / ml vs. 80 +21 ng / ml, p <0.001) compared with patients with paroxysmal AF. A significantly lower level of matrix metalloproteinase-1 (MMP-1) was observed in patients with persistent and chronic forms of AF, but the level of tissue inhibitor of matrix metalloproteinase-1 (TIMMP-1) was increased in comparison with patients with paroxysmal AF (09.67 + 4.41 ng / Ml, 11.90 + 4.79 ng / ml vs. 14.98 + 6.28 ng / ml, p = 0.03 and 187 + 49 ng / ml, 155 + 45 ng / ml vs. 130 + 38 ng / ml, p <0.001, respectively). The level of TIMMP-1 was significantly lower in the control group compared with patients with paroxysmal and persistent and chronic forms of AF (102 + 15 ng / ml, 130 +38 ng / ml, 155 + 45 ng / ml and 194 + 49 ng / ml , Respectively, p <0.001).Conclusions: The serum level of type I collagen markers differs significantly between healthy people and patients with AF. Moreover, these markers also differ depending on AF form. It can be assumed that the intensity of extracellular synthesis and degradation of type I collagen can be related to the severity and type of AF.